Radionuclide diagnosis of ureteric function in patients with stages I-IV cancer of the cervix uteri - L. A. Ashrafyan; D. K. Fomin; V. I. Trushin; A. V. Trepin (Опухоли женской репродуктивной системы, 2014)
The experience with serial renal scintigraphy demonstrated its high informative value and safety in evaluating the severity of intrarenal urine outflow disorders; however, failure to make an objective assessment of ureteral patency considerably limits its study. The set of studies, which is given in this paper, is devoted to precisely this, highly urgent, problem. The authors describe an original procedure for diagnosing impaired urine outflow along the ureters, which has been used during serial renal scintigraphy, define the visual and digital characteristics of normal and impaired urine outflow in the supravesical segment, and denote the criteria characterizing severe impair- ments of renal urine derivation along the ureters. Risk factors for urine outflow disorders have been identified in patients with cancer of the cervix uteri, who receive various treatment modalities.